Attitudes and intentions toward prostate cancer screening among males in China: a qualitative study - Hao, Shutao; Fang, Linlin; Du, Yanting; Zheng, Jin; Ou, Yufeng; Yu, Zhenghong (Frontiers in Urology, 2025)
PurposeTo explore the factors influencing prostate cancer screening willingness among the Chinese male population.MethodsThis is a qualitative study that adopted a phenomenological approach. Purposive sampling was used to recruit 21 males (aged 48–81 years, with a mean age of 57 years) from the health examination center of a tertiary hospital in Shenyang, China. Semi-structured face-to-face interviews were verbatim transcribed and independently cross-checked by two Master’s-level researchers. Data analysis was performed using MaxQDA ver.10 software and followed Colaizzi’s phenomenological analysis steps.ResultsDeductive analysis identified three core themes aligned with the Theory of Planned Behavior (TPB): Attitudes toward the Behavior (getting screened for the sake of family, primary prevention actions, meaningless, fear of the result, and don’t want family members to worry), subjective norm (family members, friends, and colleagues, and health professionals), and control beliefs (cost and insurance, limited understanding of the disease, no symptoms, unfamiliar with the PSA test, doubt screening, health examination package setting, and believe that cancer is incurable).ConclusionsThe study highlights the complex and unique factors influencing willingness to undergo prostate cancer screening in China. The findings provide insights for developing targeted interventions to address the challenges of insufficient prostate cancer screening, particularly by enhancing health professional guidance and addressing financial barriers.